Curriculum Reforms and Physical Education: the Theoretical-Conceptual knowledge of the Spanish School Population Reformas Curriculares y Educación Física: los Conocimientos Teórico-Conceptuales de la Población Escolar Española. - Juan Luis Hernández Álvarez; Roberto Velázquez Buendía; Eugenia Martínez Gorroño (Arizona State University, 2007)
This article analyses the changes generated by the implementation of a new curriculum in the context of the new Law of Education in Spain. In that context, our interest is centered in the reflection about the influence of educational policies in the development of Physical Education as a subject matter. We use a historical perspective to analyze some of the changes introduced by the Ley de Ordenación General del Sistema Educativo Español (LOGSE, 1990), and the curricular reform. In particular, we base our analysis on the introduction of the theoretical-conceptual contents (“to know”) in the curricular area of Physical Education, which has traditionally centered in the “know how”. In order to carry out our analysis, we took as a point of departure the results obtained from the research on what the Spanish school population knows about the theoretical-conceptual contents. The focus of the investigation was the Spanish school population between the ages of 10 and 16. A Questionnaire on the Learning of Concepts in PE was applied to a representative sample (n=2,721) of the said school population. Results show that, in general, the students of both primary and secondary education have a poor theoretical and conceptual knowledge, reaching worrying proportions in some cases. The results also show the need to develop strategies that lead the improvement of the “PE culture” among students of both primary and secondary education. The learning of these contents is a fundamental factor in the education of autonomous citizens, committed to caring for their bodies and their health, and thus achieving a good quality of life. The study shows that the curricular reform by itself is insufficient to introduce new contents. Thus it is also necessary to implement measures of support to teachers so that the proposed changes become a reality. El objeto central de este artículo es realizar una reflexión sobre la influencia de las políticas educativas en la evolución de la asignatura de Educación Física en el sistema educativo español. Tomando una cierta perspectiva histórica, se analizan algunos de los cambios introducidos por la Ley de Ordenación General del Sistema Educativo Español (LOGSE, 1990) y por las reformas curriculares que la sucedieron. En concreto, el análisis se basa en la introducción de los contenidos teórico-conceptuales ("saber") en un área curricular tradicionalmente centrada en el "saber hacer". En este sentido, tomando como punto de partida los resultados de la investigación sobre la adquisición de conceptos por parte de la población escolar , se establecen conclusiones del estado actual del conocimiento en este ámbito y se ofrecen recomendaciones sobre la necesidad de mejorar la adquisición de dichos contenidos, "saber" y "comprender", en orden a una mejor contribución de la Educación Física al desarrollo personal y social de los sujetos y a su autonomía respecto de la práctica de una actividad física saludable. La investigación realizada se centró en la población escolar española de 10 a 16 años. A una muestra representativa de dicha población (n=2.721) le fue aplicado el Cuestionario sobre Aprendizaje de Conceptos en Educación Física (CACEF). Los resultados demuestran que, en general, los alumnos de la Educación primaria y Secundaria poseen un escaso conocimiento teórico-conceptual, alcanzando proporciones preocupantes en algunos casos. Asimismo, los resultados demuestran la necesidad de desarrollar estrategias que conduzcan a mejorar la cultura en Educación Física entre los alumnos de la Educación Primaria y de la Educación Secundaria. Los cambios en el currículo se muestran insuficientes para, por sí mismos, lograr la introducción real de nuevos contenidos en una disciplina, siendo necesario implementar medidas de apoyo a los docentes para hacer realidad una reforma curricular.